Problems of harmonization in legislation and changes in the methodological approaches to accounting in budgetary institutions - Bondarenko, O.; Slipenchuk, H. (Ways to Improve Construction Efficiency, 2015)
The paper studied the inconsistencies in legislation and changes in methodological approaches to accounting of fixed assets and intangible assets in budgetary institutions.